The Effect of Design on User Comfort in the Dseign of Rest Areas and Service Facilities in Kulon Progo Regency - Dini Setiyowati; Tigor Wilfritz Soaduon Panjaitan (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
High vehicle mobility in 2025 has contributed to an increase in accident rates, with human factors being the dominant cause at 94.7%. Driver fatigue often remains unaddressed because existing Rest and Service Areas (TIP) tend to only provide physical facilities rather than mental recovery. This qualitative study aims to formulate a TIP concept that addresses the psychological needs of toll road users through a biophilic architecture approach. Through literature studies and evaluations of similar facilities, the "Pasanggrahan Rawikara" core concept was developed. This concept integrates natural elements into the design to create a space for mental recovery, reducing stress, and improving driver focus. The implementation of this design in the Kulon Progo Regency area is expected to minimize accidents caused by human fatigue factors.